Pure orientation passive positioning of UAVs in different formations and initial positions - Jiang, Minghao; Liu, Junliang; Li, Zecheng (2023 IEEE 2nd International Conference on Electrical Engineering, Big Data and Algorithms (EEBDA), 2023)
UAV positioning plays an important role in UAV formation flight. UAV positioning requires transmitting and receiving electromagnetic signals to complete, and electromagnetic signals are subject to external interference, and in order to reduce this effect, pure azimuth passive positioning is mostly used to adjust UAV positions in fleet formation positioning. In this question, a simulation model is constructed to achieve effective positioning of UAVs. The initial position of the UAV is often deviated from the ideal state. The problem is solved by using the representation of polar coordinates and the idea of greedy algorithm, the triangulation method for positioning, the idea of optimization algorithm, the adjustment of control variables one by one, and the dynamic planning algorithm, setting the adjustment step and adjustment rules to build a simulation model. The UAVs are adjusted to a cone formation with an unknown initial position, and the position of each UAV cannot be measured directly by the unknown information of passive positioning. The distance and angle between neighboring UAVs are used to measure the position deviation of the UAVs and the symmetric position relationship in the formation, and the position of the UAVs is adjusted. Then, by optimizing the strategy, as little as possible at a time to choose the transmitter. The number of UAVs that transmit signals is adjusted to the remaining UAV positions, and the dynamic planning model is used to find a solution that minimizes the deviation of the UAVs in the adjustment process, so as to obtain the optimal solution in terms of the global situation.